Timetable planning and scheduling system - Chew, Yi Zhuang. (2013)
This report presents the design, implementation and testing of a new server-client database driven web-based Timetable Planning and Scheduling System (TPS) to replace the existing version used by staff to plan and schedule lessons for the undergraduate programmes offered by the School of Computer Engineering (SCE).